Influences of structural modification of naphthalenediimides with benzothiazole on organic field-effect transistor and non-fullerene perovskite solar cell characteristics - Shaikh, Dada . (2021)
Developing air-stable high-performance small organic molecule-based n-type and ambipolar organic field-effect transistors (OFETs) is very important and highly desirable. In this investigation, we designed and synthesized two naphthalenediimide (NDI) derivatives (NDI-BTH1 and NDI-BTH2) and found that introduction of 2-(benzo[d]thiazol-2-yl) acetonitrile groups at the NDI core position gave the lowest unoccupied molecular orbital (LUMO; -4.326 eV) and displayed strong electron affinities, suggesting that NDI-BTH1 might be a promising electron-transporting material (i.e., n-type semiconductor), whereas NDI-BTH2 bearing bis(benzo[d]thiazol-2-yl)methane at the NDI core with a LUMO of -4.243 eV was demonstrated to be an ambipolar material. OFETs based on NDI-BTH1 and NDI-BTH2 have been fabricated, and the electron mobilities of NDI-BTH1 and NDI-BTH2 are 14.00 × 10-5 and 8.64 × 10-4 cm2/V·s, respectively, and the hole mobility of NDI-BTH2 is 1.68 × 10-4 cm2/V·s. Moreover, a difference in NDI-core substituent moieties significantly alters the UV-vis absorption and cyclic voltammetry properties. Thus, we further successfully employed NDI-BTH1 and NDI-BTH2 as electron transport layer (ETL) materials in inverted perovskite solar cells (PSCs). The PSC performance exhibits that NDI-BTH2 as the ETL material gave higher power conversion efficiency as compared to NDI-BTH1, that is, NDI-BTH2 produces 15.4%, while NDI-BTH1 gives 13.7%. The PSC performance is comparable with the results obtained from OFETs. We presume that improvement in solar cell efficiency of NDI-BTH2-based PSCs is due to the well-matched LUMO of NDI-BTH2 toward the conduction band of the perovskite layer, which in turn increase electron extraction and transportation.